THE EFFECT OF PROGRESSIVE MUSCULAR RELAXATION ON MANAGING ANGER - Rahman, Saifur; Ferdousi, Maria; Rahman, Mustafizur; Islam, Shariful (Psychological thought, 2025)
The aim of this study was to investigate the effectiveness of Progressive Muscular Relaxation on managing anger. A quasi-experimental one-group Pre-test and Post-test research design that was employed with a convenience sample of sixty participants. Twenty participants (12 men and 8 women, aged 18-35) who scored high on the Novaco Anger Scale-Provocation Inventory (NAS-PI) completed ten group anger management sessions, which included Progressive Muscle Relaxation. The paired sample t-test was used to compare the average scores before and following the relaxing sessions. Results showed a significant reduction in anger scores from pre-intervention (M=81.10, SD=3.19) to post-intervention (M=68.35), SD=3.66), t (19) =17.67, p .001). These findings suggest that Progressive Muscle Relaxation is an effective and accessible non-pharmacological intervention for anger management. This technique may also serve as an affordable, culturally adaptable technique for improving emotion regulation.